Pengaruh Social Media Marketing Activity Terhadap Willingness To Pay Premium Price Yang Dimediasi Oleh Brand Equity Pada Produk Skintific - Amelia Putri; Hasyim Hasyim (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
Social media marketing activities are important for companies to market their products in this digital age, where they can help companies continue to compete in the market. Therefore, this study aims to determine the size of the influence of social media marketing activity, brand awareness, brand image to willingness to pay premium price which is mediated by brand equity in Skintific products. The population in this study were people who had bought Skintific products once or more in the Jabodetabek areas. This research is a quantitative study using primary data as well as data collection techniques carried out in this study, namely using questionnaires distributed questionnaires using a Likert scale of 1-5 and distributed to 114 respondents. The analytical tool used in this study is Structural Equation Model (SEM). The findings in this study show that social media marketing activity, brand awareness, brand image, brand loyalty have a significant effect on willingness to pay premium price. Then, this study has limitations, namely the number of samples that are still not large enough to describe the actual situation.